Vaccine-linked chemotherapy improves cardiac structure and function in a mouse model of chronic Chagas disease - Jones, Kathryn M.; Mangin, Elise N.; Reynolds, Corey L.; Villanueva, Liliana E.; Cruz, Julio Vladimir; Versteeg, Leroy; Keegan, Brian; Kendricks, April; Pollet, Jeroen; Gusovsky, Fabian; Bottazzi, Maria Elena; Hotez, Peter J. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Chagas disease, caused by chronic infection with the protozoan parasite Trypanosoma cruzi, affects 6-7 million people worldwide. The major clinical manifestation of Chagas disease is chronic Chagasic cardiomyopathy (CCC), which encompasses a spectrum of symptoms including arrhythmias, hypertrophy, dilated cardiomyopathy, heart failure, and sudden death. Current treatment is limited to two antiparasitic drugs, benznidazole (BNZ) and nifurtimox, but both have limited efficacy to halt the progression of CCC. We developed a vaccine-linked chemotherapy strategy using our vaccine consisting of recombinant Tc24-C4 protein and a TLR-4 agonist adjuvant in a stable squalene emulsion, in combination with low dose benznidazole treatment. We previously demonstrated in acute infection models that this strategy parasite specific immune responses, and reduced parasite burdens and cardiac pathology. Here, we tested our vaccine-linked chemotherapy strategy in a mouse model of chronic T. cruzi infection to evaluate the effect on cardiac function. Methods Female BALB/c mice infected with 500 blood form T. cruzi H1 strain trypomastigotes were treated beginning 70 days after infection with a low dose of BNZ and either low or high dose of vaccine, in both sequential and concurrent treatments streams. Control mice were untreated, or administered only one treatment. Cardiac health was monitored throughout the course of treatment by echocardiography and electrocardiograms. Approximately 8 months after infection, endpoint histopathology was performed to measure cardiac fibrosis and cellular infiltration. Results Vaccine-linked chemotherapy improved cardiac function as evidenced by amelioration of altered left ventricular wall thickness, left ventricular diameter, as well as ejection fraction and fractional shortening by approximately 4 months of infection, corresponding to two months after treatment was initiated. At study endpoint, vaccine-linked chemotherapy reduced cardiac cellular infiltration, and induced significantly increased antigen specific IFN-γ and IL-10 release from splenocytes, as well as a trend toward increased IL-17A. Discussion These data suggest that vaccine-linked chemotherapy ameliorates changes in cardiac structure and function induced by infection with T. cruzi. Importantly, similar to our acute model, the vaccine-linked chemotherapy strategy induced durable antigen specific immune responses, suggesting the potential for a long lasting protective effect. Future studies will evaluate additional treatments that can further improve cardiac function during chronic infection.